SYNTHESIS OF CATIONIC MACROMONOMERS BY LIAVING POLYMERIZATIONS FOR COMB-BRANCHED POLYELECTROLYTES - Zeng, Faquan (My University, 2001)
Cationic macromonomers of poly [2-(dimethylamino) ethyl methacrylate dimethyl sulfate] polyDMAEMA-DMS) were synthesized by both living nitro-anionic polymerization with a novel capping technique and atom-transfer radical polymerization (ATRP). The macromonomers were copolymerized with acrylamide to give well-defined comb-branched polyelectrolytes having polyacrylamide (PAM) backbone and polyDMAEMA-DMS side chains by free radical processes. First, the radical mechanism involved in ATRP was investigated using an electron spin resonance (ESR) spectrometer and a differential scanning calorimeter (DSC). Poly (ethylene glycol) dimethacrylate (PEGDMA) was used as a model system for this purpose of mechanism elucidation. The network-forming feature of the system imposed diffusion limitations to radical deactivation reactions and thus allowed us to directly observe the radical intermediates during the polymerization by the first time. The polyDMAEMA macromonomers bearing terminal allyl moieties were synthesized by the A TRP method using allyl-containing organic halide as initiator. The polyDMAEMA macromonomers with styrenic end groups were prepared by the living nitro-anionic polymerization. A novel capping technique was developed to improve the initiator efficiency in the anionic polymerization. The polyDMAEMA macromonomers were quatemized with dimethyl sulfate yielding cationic polyDMAEMA-DMS macromonomers. The copolymerization of acrylamide with polyDMAEMA-DMS macromonomers was conducted using 2,2'-azobis(2-methylpropionamidine) dihydrochloride (AlBA) as free radical initiator in aqueous solution. The reactivity ratios in copolymerization were measured for the two series of cationic macromonomers with terminal styrenic or allyl groups. PolyDMAEMA-DMS macromonomer with styrenic end group was found to have a much higher reactivity than acrylamide. It was attributed to the hydrophobic characteristic of styrenic group and the micelle formation of the macromonomer in aqueous media. In contrast, the PolyDMAEMA-DMS macromonomer with terminal allyl group had lower reactivity than acrylamide. This difference in reactivities caused a chemical composition drifting during the copolymerization. A semi-batch method was used to control the copolymer composition for synthesizing comb-branched cationic polyelectrolytes.
Keywords: Chemical Engineering; Chemical Engineering